PLS Financing and Stability of Indonesian Islamic Banking - widarjono, agus (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2022)
Islamic banks are prohibited from using interest rates in any transaction, including financing. Instead, Islamic banks apply a profit-loss sharing (PLS) and non-PLS contract system. PLS financing consists of Musyarakah and Mudharabah. Our study analyzes the extent to which PLS financings with some control variables influence the stability of Islamic banks. This study measures stability utilizing Z-score. We employ the Autoregressive distributed lag (ARDL) model using monthly aggregate data of Islamic banks, covering from 2010:M1 to 2019:M12. According to the bound testing approach, the long-run relationship between dependent and explanatory variables is found. The PLS financings strengthen Islamic banks' stability for which Musyarakah financing enhances the stability but Mudharabah financing weakens stability. Evidence also underlines that bank characteristics such as CAR and efficiency affect stability. High CAR boosts stability but low efficiency deteriorates stability. More importantly, macroeconomic conditions persistently support stability for which economic upturn fortifies stability but sharp depreciation weakens stability.